Rediscovering the Person in the Adolescent Mother: Bringing her looks to herself - Arguedas-Ramírez, Ana (2021)
“Rediscovering the person in the adolescent mother” is a change in the approach to this condition by rescuing, in priority order, the adolescent situation in which the person is situated. It is a condition where a series of sudden changes are generated. In addition, these changes entail new demands in parallel to her adolescence, pregnancy condition, and the responsibilities for the young woman and her family.In this process, the construction of knowledge and attitudes are promoted in order to empower the adolescent mother in her own rediscovery through her participation in spaces for self-reflection, from the vision of herself and as a person with rights.Rediscovery is the methodology designed to ease the learning and behavior change respecting to herself. It is based on her feelings, fears, difficulties as basic inputs for internalizing new knowledge, attitudes, and skills.This experience has been carried out for four years (2015-2018), in which the Institute for Interdisciplinary Studies on Childhood and Adolescence (INEINA), together with the San Vicente de Paúl Hospital and the Child Welfare Office (PANI), in an interdisciplinary, transdisciplinary, and inter-institutional action, achieved joint efforts in the generation of their own reflections on the people, their families, and participating institutions.